Pengaruh Umur Perusahaan, Intensitas Persediaan, dan Pertumbuhan Penjualan terhadap Penghindaran Pajak - Siti Rohimah; Khusnul Khuluqi (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2026)
This study empirically investigates the effects of firm age, inventory intensity, and sales growth on tax avoidance among property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative approach was employed using secondary data extracted from annual financial statements. The sample comprised 80 firm-year observations from 16 companies selected through purposive sampling. Panel data regression analysis was conducted using the Random Effects Model (REM). The findings reveal that firm age and inventory intensity significantly influence tax avoidance, whereas sales growth exhibits no significant effect. Collectively, the three explanatory variables significantly affect tax avoidance. These findings provide robust empirical evidence that firm-specific characteristics, particularly organizational maturity and inventory structure, constitute important determinants of corporate tax avoidance within Indonesia's property and real estate industry.